Estetika Resepsi Sastra dalam Ragam Tanggapan Naẓm Alfiyyah Ibn Mālik - Rohman, Muhammad Ariffur (Study Program of Arabic Language Teaching, 2022)
This study reveals the various responses to the text of Nazm Alfiyyah Ibn Malik's stanza that developed in Indonesia, especially among Islamic boarding schools. The author uses the aesthetic theory of literary reception by placing Naẓm Alfiyyah Ibn Mālik as a literary text. The results of this study are; The Islamic Boarding School gave birth to two models of responses, responses in the form of works as a whole and responses partially. The first model of Islamic boarding school has a relatively similar response to that of Arab Islamic scholars, tends to be textual so that it is only able to fill a small part of the space in the text of the Nazm Alfiyyah stanza. The second model of Islamic boarding schools gave birth to responses that tended to be contextualistic, out of the nahwu-sarf discussion so that they were able to fill more empty spaces than the first group. From the academics who gave birth to a scientific paper, the response of this group was relatively the same as the first model Islamic boarding school, only the reading process was carried out partially and strictly followed established scientific rules. The creative reader community, who are widely circulated in cyberspace (social media) have responses that tend to be strange (weird), out of habits (rules) that have been established both among Arab Islamic scholars, Islamic boarding schools, and academics.